An interdisciplinary family-centered program: An innovative approach to better meet the multifaceted needs of grandparent-headed families. Issue 3 (27th May 2018) - Lee, Youjung; Anderson, Elizabeth; Quranta, Judith; Shim, Bonggu
ABSTRACT: An innovative interdisciplinary family-centered pilot program for grandparent-headed families was developed and evaluated by university faculty from social work, education, nursing, and physics using a community–university partnership model. This pilot study aims to explore the potential for an interdisciplinary family-centered program to address some of the multifaceted education, psychosocial, and physical health needs of grandparent-headed families. A qualitative evaluation of this pilot study reveals that an interdisciplinary family-centered program can be effective for increasing custodial grandparents' feelings of self-efficacy around supporting their grandchildren's education and understandings of the importance of self-care. Emerging findings from this pilot study suggest that an interdisciplinary family-centered program has the potential to offer innovative ways for addressing the multifaceted needs of grandparent-headed families while fostering new means for family and community engagement.